A systematic literature review of cloud kitchen - Harini, P; Rohini, A; Selvanayaki, S; Prahadeeswaran, M; Selvi, R P; Shokila, C (Plant Science Today, 2025)
The concept of cloud kitchens, or ghost kitchens, has emerged as a transformative trend in the food service industry, offering an economical and efficient model that eliminates the need for physical dining spaces and focuses solely on delivery and takeout. This approach provides several advantages, including reduced overhead costs, operational efficiency, scalability and expanded market reach through virtual platforms. However, market saturation, building brand visibility and maintaining food quality remain significant hurdles. Future trends may involve multi-brand operations within a single kitchen, advanced technology integration, eco-friendly practices and suburban and rural areas expansion. By addressing these challenges, ghost kitchens can capitalise on their innovative potential to reshape the food service landscape.